Effects of Lorentz violation in superconductivity. (1st December 2021) - Furtado, J.; Costa Filho, R. M. M.; Morais, A. F.; Jardim, I. C.
Abstract: This paper presents the effects of Lorentz violation in superconductivity. Constructing a Lorentz-violating Ginzburg-Landau theory of superconductivity we discuss the influence of the Lorentz-violating tensors and in London's penetration depth, in the coherence length and critical magnetic field.